2020
DOI: 10.21203/rs.3.rs-23943/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LINC02418 promotes colon cancer progression by suppressing apoptosis via interaction with miR-34b-5p/BCL2 axis

Abstract: Background LncRNAs have been demonstrated to be functional regulators in tumor progression through interaction with various signaling pathways in multiple cancer types. However, the effect of LINC02418 on CRC progression still remains unclear. Methods LncRNA expression profile in CRC tissues was explored by using the TCGA database. The expressional level of LINC02418 in CRC patients was confirmed by qRT-PCR. Kaplan-Meier analyses was used to investigate the correlations between LINC02418 and OS of patients wit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…For instance, miR-34b-5p was induced by p53 to block NF-jB-inducing kinase and therefore inhibit noncanonical NF-jB signaling [22]. Overexpression of miR-34b-5p promoted tumor cell apoptosis in serval cancers, including thyroid carcinoma [23], colorectal cancer [24], and oral cancer [25]. Also, miR-34b-5p mediated recurrent seizures-induced apoptosis of hippocampal astrocytes [9].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, miR-34b-5p was induced by p53 to block NF-jB-inducing kinase and therefore inhibit noncanonical NF-jB signaling [22]. Overexpression of miR-34b-5p promoted tumor cell apoptosis in serval cancers, including thyroid carcinoma [23], colorectal cancer [24], and oral cancer [25]. Also, miR-34b-5p mediated recurrent seizures-induced apoptosis of hippocampal astrocytes [9].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that expression of CRNDE was abnormally increased in tumors, and the KM survival analysis plot revealed that it was closely related to the prognosis of cancer patients. In the study by Tian et al (24), LINC02418 expression was found to be up-regulated in human colon cancer samples compared with adjacent tissues, and its high expression level was associated with poor prognosis of CRC patients and could be used as an indicator to predict prognosis. The results of another study (25) suggested that BLACAT1, as a cell cycle regulator, may be a potential target for the prevention and treatment of human colon cancer.…”
Section: Discussionmentioning
confidence: 98%